"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis